Prevalence and Characterization of Staphylococcus aureus Isolated From Women and Children in Guangzhou, China - Liang, Bingshao; Mai, Jialiang; Liu, Yunfeng; Huang, Yanmei; Zhong, Huamin; Xie, Yongqiang; Deng, Qiulian; Huang, Lianfen; Yao, Shuwen; He, Yanming; Long, Yan; Yang, Yiyu; et al. (Frontiers in Microbiology, 2018)
The prevalent Staphylococcus aureus clones and antibiotic susceptibility profiles are known to change dynamically and geographically; however, recent S. aureus strains causing infections in women and children in China have not been characterized. In this study, we analyzed the molecular epidemiology and antimicrobial resistance of S. aureus isolated from patients in four centers for women and children in Guangzhou, China. In total, 131 S. aureus isolates (100 from children and 31 from women) were analyzed by spa typing, multi-locus sequence typing, virulence gene and antimicrobial resistance profiling, staphylococcal chromosomal cassette mec typing, and mutation analyses of rpoB. A total of 58 spa types, 27 sequence types (STs), and 10 clonal complexes (CCs) were identified. While CC59 (ST59-IV, 48.8%; ST338-III, 35.7%) and CC45 (ST45-IV, 100%) were the major clones (84.4%) among MRSA isolates, CC5 (ST188, 24.3%; ST1, 21.6%) and CC398 (ST398, 70%) were the major ones (70.1%) among MSSA isolates. ST338-MRSA-III mostly found in pus but hardly in respiratory tract samples while ST45-MRSA-IV was on the opposite, even though they both found in blood sample frequently. Staphylococcal enterotoxin genes seb-seq-sek were strongly associated with ST59 and ST338, while sec was associated with ST45, ST121, ST22, and ST30. All ST338, ST1232, and SCCmec III isolates carried lukF/S-PV genes. A total of 80% of ST338 isolates were resistant to erythromycin, clindamycin, and tetracycline. All ST45 isolates exhibited intermediate or complete resistance to rifampicin. In total, 481 HIS/ASN mutations in rpoB were found in rifampicin-resistant or intermediate-resistant isolates. ST338-III and ST45-IV emerged as two of three major clones in MRSA isolates from women and children in Guangzhou, China, though ST59-MRSA-IV remained the most prevalent MRSA clone. Clonal distribution of S. aureus varied, depending on the specimen source. Virulence genes and antibiograms were closely associated with the clonal lineage. These results clarified the molecular epidemiology of S. aureus from women and children in Guangzhou, China, and provide critical information for the control and treatment of S. aureus infections.